The new girl : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2019)
She was covered from head to toe in expensive wool and plaid, the sort of stuff one saw at the Burberry boutique in Harrods. She carried a leather bookbag rather than a nylon backpack. Her patent leather ballet slippers were glossy and bright. She was proper, the new girl, modest. But there was something else about her <U+2026> At an exclusive private school in Switzerland, mystery surrounds the identity of the beautiful raven-haired girl who arrives each morning in a motorcade fit for a head of state. She is said to be the daughter of a wealthy international businessman. In truth, her father is Khalid bin Mohammed, the much-maligned crown prince of Saudi Arabia. Once celebrated for his daring social and religious reforms, he is now reviled for his role in the murder of a dissident journalist. And when his only child is brutally kidnapped, he turns to the one man he can trust to find her before it is too late. What<U+2019>s done cannot be undone <U+2026> Gabriel Allon, the legendary chief of Israeli intelligence, has spent most of his life fighting terrorists, including the murderous jihadists financed by Saudi Arabia. Prince Khalid<U+2014>or KBM, as he is known<U+2014>has pledged to finally break the bond between the Kingdom and radical Islam. For that reason alone, Gabriel regards him as a valuable if flawed partner. Together they will become unlikely allies in a deadly secret war for control of the Middle East. The life of a child, and the throne of Saudi Arabia, hang in the balance. Both men have made their share of enemies. And both have everything to lose.